REGULASI DIRI, LINGKUNGAN SEJAWAT, DAN TASK AVERSIVENESS TERHADAP PROKRASTINASI AKADEMIK - Febrianti , Dika Melia; Mayasari , Viviana; Wardani , Nevita Arda (Fakultas Psikologi Universitas Tarumanagara, 2025)
This research is motivated by the high level of academic procrastination among students, which negatively impacts academic performance. The main objective of this study is to analyze the influence of self-regulation, peer environment, and task aversiveness on academic procrastination among students in the S1 Economic Education study program. The urgency of this research lies in the importance of understanding the factors that influence procrastination behavior to develop preventive strategies. The variables examined include self-regulation, defined as students' ability to manage their learning processes; peer environment, encompassing interactions and support among peers; and task aversiveness, referring to negative perceptions of tasks. The measurement tool used is a questionnaire consisting of 45 statements, distributed online to 106 respondents using simple random sampling. The research method employed is descriptive quantitative with regression analysis to test the relationships among the variables. The results indicate that self-regulation and peer environment have no significant effect on academic procrastination, while task aversiveness has a positive and significant impact. The conclusions drawn from this study emphasize the need for attention to task aversiveness in efforts to reduce academic procrastination among students.